THE ROLE OF A PHYSICAL EDUCATION TEACHER IN THE DEVELOPMENT OF SPEED AND STRENGTH QUALITIES OF SCHOOLCHILDREN - ATHLETES (Academicia Globe: Inderscience Research, 2022)
An important characteristic feature of sports training is the leading role of the coach with a sufficiently high degree of independence of athletes. In the field of education, the leading role of the coach in a broad sense lies in the fact that, in addition to his direct influence on the athlete, he must work closely with all other persons who have an educational impact on him and coordinate their activities, the leadership role of the coach should not be reduced to guardianship or petty care. Sports heights are inconceivable without the independent mind and actions of the athlete, his activity, without creative cooperation with the coach. These qualities are a prerequisite for successful performance in competitions.